The complete sequence of a Spanish isolate of Broad bean wilt virus 1 (BBWV-1) reveals a high variability and conserved motifs in the genus Fabavirus - Ferrer, Rosa M.; Guerri, José; Luis-Arteaga, Marisol; Moreno, Pedro; Rubio, Luis (2017)
The genome of a Spanish isolate of Broad bean wilt virus-1 (BBWV-1) was completely sequenced and compared with available sequences of other isolates of the genus Fabavirus (BBWV-1 and BBWV-2). This consisted of two RNAs of 5814 and 3431 nucleotides, respectively, and their organization was similar to that of other members of the family Comoviridae. Its mean nucleotide identity with a BBWV-1 American isolate was 81.5%, and between 59.8 and 63.5% with seven BBWV-2 isolates. Our analysis showed sequence stretches in the 5′ non-coding regions which are conserved in both genomic RNAs and in BBWV-1 and BBWV-2 isolates.